Relationship of lower uterine segment cancer with Lynch syndrome: A novel case with an hMLH1 germline mutation - MASUDA, KENTA (D.A. Spandidos, 2012)
Lynch syndrome is a genetic disease that often develops in patients with endometrial cancer and is caused by abnormal DNA mismatch repair (MMR) genes. In the United States, it was recently reported that the prevalence of Lynch syndrome with an hMSH2 mutation in patients with endometrial cancer in the lower uterine segment (LUS) is much greater than that in patients with endometrial cancer, although no such reports have been published in Asia. In this study, we examined the correlation between endometrial cancer in LUS and abnormalities in MMR genes. We examined 625 patients, who were diagnosed with endometrial cancer and underwent a hysterectomy. Nine patients (1.4%) had cancer based on pathological confirmation of a tumor in the lower part of the uterus and no cancer in the upper part. These cases were compared with 27 cases of sporadic endometrial (non-LUS) cancer. The age and BMI of the patients with LUS cancer were significantly lower than those of the patients with non-LUS cancer. No differences were observed in the pathological characteristics. The microsatellite instability (MSI)-positive rates were similar. Immunohistochemistry showed a decreased expression of hMLH1 and hMSH6 in patients with LUS cancer. In contrast with earlier reports from the United States, hMSH2 was expressed in all the cases. Of the 2 patients with LUS cancer who exhibited high MSI, 1 patient showed abnormal methylation of hMLH1, while the other patient was diagnosed with Lynch syndrome with a mutation in the hMLH1 gene. This is the second report on the relationship of LUS cancer and Lynch syndrome, and the first to describe an Asian patient with LUS cancer with Lynch syndrome induced by an hMLH1 mutation.